Measuring work and workers: Wearables and digital assistance systems in manufacturing and logistics - Martin Krzywdzinski; Sabine Pfeiffer; Maren Evers; Christine Gerber (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2022)
The smart glove or smart data glasses: Digitalization of work means that technology is moving closer to the bodies of employees. It can make movements, vital signs and even emotions visible. Technologies which many people use privately to monitor their sporting activities or health opens up a new dimension of control in the workplace, but also the possibility of supporting employees in complex work processes. Based on case studies of companies in manufacturing and logistics as well as a survey of employees, this study provides insights into operational use cases of wearables and the assessments of employees. It reveals contradictory experiences and a high importance of co-determination and co-design of new technologies by employees and works councils as a condition for using new technologies for improving work quality. – – Der intelligente Arbeitshandschuh oder die smarte Brille: Mit der Digitalisierung rückt Technologie eng an den Körper der Beschäftigten. Bewegungen, Vitalzeichen und selbst Emotionen können damit sichtbar werden. Was viele privat gerne nutzen zur Kontrolle von sportlichen Aktivitäten oder dem Monitoring der Gesundheit, eröffnet am Arbeitsplatz eine neue Dimension der Kontrolle, aber auch die Möglichkeit der Unterstützung der Beschäftigten in komplexen Arbeitsprozessen. Basierend auf Fallstudien von Unternehmen in der Fertigung und Logistik sowie einer Befragung von Beschäftigten gibt die Studie Einblicke in betriebliche Anwendungsfälle von Wearables und die Einschätzungen von Beschäftigten. Es zeigen sich widersprüchliche Erfahrungen und eine hohe Bedeutung der Mitbestimmung und der Mitgestaltung neuer Technologien durch Beschäftigte und Betriebsräte.
Keywords: J51; J52; J81; O33; 330; technological change; digitalization; manufacturing; logistics; work organization; skills; works councils; Technologischer Wandel; Digitalisierung; Fertigung; Logistik; Arbeitsorganisation; Qualifikationen; Betriebsräte